Complex IV subunit isoform COX6A2 protects fast‐spiking interneurons from oxidative stress and supports their function. (3rd August 2020) - Sanz‐Morello, Berta; Pfisterer, Ulrich; Winther Hansen, Nikolaj; Demharter, Samuel; Thakur, Ashish; Fujii, Katsunori; Levitskii, Sergey A; Montalant, Alexia; Korshunova, Irina; Mammen, Pradeep PA; Kamenski, Piotr; Noguchi, Satoru; et al.
Abstract: Parvalbumin‐positive (PV + ) fast‐spiking interneurons are essential to control the firing activity of principal neuron ensembles, thereby regulating cognitive processes. The high firing frequency activity of PV + interneurons imposes high‐energy demands on their metabolism that must be supplied by distinctive machinery for energy generation. Exploring single‐cell transcriptomic data for the mouse cortex, we identified a metabolism‐associated gene with highly restricted expression to PV + interneurons: Cox6a2, which codes for an isoform of a cytochrome c oxidase subunit. Cox6a2 deletion in mice disrupts perineuronal nets and enhances oxidative stress in PV + interneurons, which in turn impairs the maturation of their morphological and functional properties. Such dramatic effects were likely due to an essential role of COX6A2 in energy balance of PV + interneurons, underscored by a decrease in the ATP‐to‐ADP ratio in Cox6a2 − / − PV + interneurons. Energy disbalance and aberrant maturation likely hinder the integration of PV + interneurons into cortical neuronal circuits, leading to behavioral alterations in mice. Additionally, in a human patient bearing mutations in COX6A2, we found a potential association of the mutations with mental/neurological abnormalities. Synopsis: Whether brain neurons firing at high frequency depend on distinct metabolic machineries to satisfy their increased energy demands remains unclear. Here, combined genetic, functional and behavioural analyses reveal a selective role for the oxidative phosphorylation in stress protection of interneuron by safeguarding their energy supply. Mitochondrial complex IV subunit isoform Cox6a2 is enriched in parvalbumin‐positive (PV + ) interneurons in the adult rodent, rhesus monkey, and human brain. PV + interneuron‐specific Cox6a2 ablation decreases cellular ATP levels and increases oxidative stress in mice. Cox6a2 loss impairs transcriptional and morphological maturation during postnatal stages. Adult Cox6a2‐depleted PV + interneurons are hyperexcitable and defective in repetitive firing. Cox6a2 depletion results in hyperactivity in vivo . Abstract : High‐frequency‐firing brain interneurons rely on cell type‐specific energy metabolism to avoid oxidative stress.